Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1126/sciadv.abj3220
|View full text |Cite
|
Sign up to set email alerts
|

First source-to-sink monitoring shows dense head controls sediment flux and runout in turbidity currents

Abstract: Until recently, despite being one of the most important sediment transport phenomena on Earth, few direct measurements of turbidity currents existed. Consequently, their structure and evolution were poorly understood, particularly whether they are dense or dilute. Here, we analyze the largest number of turbidity currents monitored to date from source to sink. We show sediment transport and internal flow characteristic evolution as they runout. Observed frontal regions (heads) are fast (>1.5 m/s), thin (<… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 90 publications
2
33
0
Order By: Relevance
“…35 ) in which faster turbidity current fronts comprise a dense (>20-40% volume) near-bed layer, in which grains do not settle individually, and which is weakly turbulent. Field evidence from Congo Canyon and elsewhere suggests faster turbidity currents contain such a dense near-bed layer at their front, while slower moving flows lack a dense layer 33,34,59 . Behaviour of this dense layer may depend on variations in excess pore pressures, dense layer thickness, substrate properties and erosion rates 60,61 , rather than settling velocity of individual grains.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…35 ) in which faster turbidity current fronts comprise a dense (>20-40% volume) near-bed layer, in which grains do not settle individually, and which is weakly turbulent. Field evidence from Congo Canyon and elsewhere suggests faster turbidity currents contain such a dense near-bed layer at their front, while slower moving flows lack a dense layer 33,34,59 . Behaviour of this dense layer may depend on variations in excess pore pressures, dense layer thickness, substrate properties and erosion rates 60,61 , rather than settling velocity of individual grains.…”
Section: Discussionmentioning
confidence: 99%
“…Changes in the front speed of turbidity currents with distance have only been measured in detail at five sites 4,24,25,34,35,58,59 . However, three key observations emerge from four locations where flows were confined within canyons-channels (Figs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on these examples, it is plausible that rare and extreme events may also affect the OC burial efficiency and distribution in Bute Inlet, potentially increasing our burial efficiency estimate. It was recently shown that most turbidity currents (∼90%) dissipate within the shallowest‐water (<200 m depth and <12 km along channel from the Homathko Delta) part of Bute Inlet, whereas less frequent (∼10%) events rework this material and progressively shuffle it downstream to the lobe (Heijnen et al., 2022; Pope et al., 2022). We further suspect that rare long runout events can flush material to the distal flat basin, as evidenced by thick sandy accumulations found at >3 m depth in 8‐m‐long piston cores collected in the distal basin at the location of core 15 (Figure 3, Heerema, 2021).…”
Section: Discussionmentioning
confidence: 99%